Service Quality Model with Cultural Perspective in Effect on Patient Satisfaction in Hospitals with Different Accreditation Status (Medico Legal Update, 2019)
There is a problem in achieving the accreditation status of hospitals in Indonesia and their understanding. The existence of an accreditation process is designed to improve the safety culture and quality culture in the hospital, so that the hospital will always strive to improve the quality of its services. The purpose of this study is the implementation of indicators of quality culture and safety culture for the development of indicators of dimensions of hospital service quality with different accreditation statuses. This type of research is observational research for the development of models from the Quality Dimensions of Services. Conducted in private hospitals in Central Java and Yogyakarta Special Region in April to August 2017. The study population was patients who were treated surgically, aged between 20 and 70 years. A total of 190 patients were collected proportionally from 5 private hospitals based on their accreditation status strata. The result is a positive relationship between Quality Culture and Service Quality, There is a positive relationship between the Culture of Safety and Service Quality, a Accreditation Status positively meaningful with Service Quality, Service Quality is positively related to Patient Satisfaction and There is a significant positive relationship indirectly between Accreditation Status and Patient Satisfaction.